Численный анализ аэроупругих характеристик турбинной ступени в трехмерном потоке вязкого газа - Гнесин, Виталий Исаевич; Колодяжная, Любовь Владимировна (НТУ "ХПИ", 2008)
Розроблено математичну модель та чисельний метод розрахунку просторових нестаціонарних в’язких течій в ступенях турбомашин на основі розв’язання зв’язаної задачі нестаціонарної аеродинаміки та пружних коливань лопаток. Проведено чисельний аналіз нестаціонарної взаємодії аеродинамічних сил, діючих на лопатки, та пружних коливань лопаток на номінальному та частковому режимах роботи останньої ступені парової турбіни 200 МВт.

The mathematical model and numerical method for calculation of 3D unsteady viscous flows in a turbomachine stage with taking into account the elastic blade oscillations on the base of solving the coupled problem of unsteady aerodynamics and elastic blades vibrations are developed. There performed the numerical analysis of unsteady interaction of aerodynamical forces acting on blades and elastic blade oscillations for the steam turbine last stage 200 MW on nominal and partial regimes.
The numerical analysis of aeroelastic characteristics for the turbine stage in 3D viscous gas flow
Keywords: нестационарные явления; аэродемпфирование; лопаточные венцы; турбулентность Болдвина-Ломакса